2008
DOI: 10.1063/1.2959826
|View full text |Cite
|
Sign up to set email alerts
|

Field emission from a single carbon nanofiber at sub 100nm gap

Abstract: The authors report the electron field emission from a single carbon nanofiber (CNF) over a range of anode to CNF tip separations of 20–5500nm. Our results show that the field enhancement factor γ is associated with the electrode separation (S). The modified Miller equation is a reasonable empirical model to describe the behavior of γ, which varies with S over a large range of values. The γ approaches to an asymptotic value of 415 or 1 when S is very large or very small as compared to the length of the CNF, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 18 publications
3
11
0
Order By: Relevance
“…It should be noted that besides the surface properties, ␤ is also dependent on D as was recently demonstrated. 18 For the 50 nm sample, the slope of the graph is found to be ϳ0.5 for V Ͻ ϳ 1 V which shows the onset of QSCL ͑at ϳ0.4 V the ratio D / o ϳ 35͒. The transition from the FN to the QSCL occurs at a much lower V as expected and shown in Fig.…”
supporting
confidence: 51%
“…It should be noted that besides the surface properties, ␤ is also dependent on D as was recently demonstrated. 18 For the 50 nm sample, the slope of the graph is found to be ϳ0.5 for V Ͻ ϳ 1 V which shows the onset of QSCL ͑at ϳ0.4 V the ratio D / o ϳ 35͒. The transition from the FN to the QSCL occurs at a much lower V as expected and shown in Fig.…”
supporting
confidence: 51%
“…However, the finite tip-anode distance is comparable to or even smaller than the tip height, as is often the case in experiments. 21,31,32 Recent studies 33,34 on the effects of finite A-K gap focus only on emitters with vertical walls, where the current rectification behaviors remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…31 It has been observed that the FE properties strongly depend on graphene-anode (Pt-Ir nanoprobe) distance, unlike the macroscopic FE measurements. [30][31][32] Again, we can directly observe the emitting behaviors of a suspended bi-layer graphene correlating structural changes with the demonstrated technique. Figure 4(a) shows TEM image of the graphene sheet before and after FE measurement were obtained.…”
mentioning
confidence: 96%
“…The FN plots can be fitted fairly well by a straight line signifying that FE of the single graphene sheet follows FN model. 30 microscope. 31 It has been observed that the FE properties strongly depend on graphene-anode (Pt-Ir nanoprobe) distance, unlike the macroscopic FE measurements.…”
mentioning
confidence: 99%